2015
DOI: 10.1088/0004-637x/811/2/147
|View full text |Cite
|
Sign up to set email alerts
|

THE PROGENITOR OF THE TYPE IIb SN 2008ax REVISITED

Abstract: Hubble Space Telescope observations of the site of the supernova (SN) SN 2008ax obtained in 2011 and 2013 reveal that the possible progenitor object detected in pre-explosion images was in fact multiple. Four point sources are resolved in the new, higher-resolution images. We identify one of the sources with the fading SN. The other three objects are consistent with single supergiant stars. We conclude that their light contaminated the previously identified progenitor candidate. After subtraction of these st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 49 publications
10
77
0
Order By: Relevance
“…Their progenitors (or strong candidates) have also been identified (Maund et al 2004(Maund et al , 2011Van Dyk et al 2014;Folatelli et al 2015). In Table 1, characteristic properties of these progenitors are listed.…”
Section: Introductionmentioning
confidence: 94%
“…Their progenitors (or strong candidates) have also been identified (Maund et al 2004(Maund et al , 2011Van Dyk et al 2014;Folatelli et al 2015). In Table 1, characteristic properties of these progenitors are listed.…”
Section: Introductionmentioning
confidence: 94%
“…39 [103,104]. Most recent observations and phenomenological modeling by [105] suggest that the progenitor was in a binary system and may have had a blue-supergiant appearance and an extended (30 − 40 R ) low-density (thus, low-mass) hydrogen-rich envelope at the time of explosion. To be conservative, we add an additional day to account for the uncertainty in shock propagation time and define the GW on-source window as II.…”
Section: Identifiermentioning
confidence: 99%
“…Aldering et al 1994;Maund et al 2004;van Dyk et al 2011;Folatelli et al 2014;Fox et al 2014;Maeda et al 2014;Folatelli et al 2015), and a WR progenitor was ruled out for SN 2008ax (Folatelli et al 2015) although the proposed binary companion of the SN 2011dh progenitor was disputed by Maund et al (2015a). Maeda et al (2015) found that the more extended progenitors may still be undergoing binary interaction, while for the less extended ones this phase would be over.…”
Section: Introductionmentioning
confidence: 99%
“…Maeda et al (2015) found that the more extended progenitors may still be undergoing binary interaction, while for the less extended ones this phase would be over. The detected type IIb progenitors have been identified as yellow or blue supergiants (YSGs or BSGs, respectively) with initial masses between 13 and 19 M (van Maund et al 2011;van Dyk et al 2014;Folatelli et al 2015).…”
Section: Introductionmentioning
confidence: 99%